Understanding and adopting DevOps in a highly regulated environment - Halmetoja, Heini (My University, 2023)
The purpose of this thesis is to evaluate whether the DevOps is suitable for use in a case company which operates in a highly regulated environment and does DevOps meet the regulations in that domain and whether it brings any added value to the case company’s software development. To answer these questions, a literature review of key reports on DevOps, a literature review of common regulations in highly regulated environment relevant in the European Union market area, and case study that included studying the processes and interviewing subject matter experts in the case company were conducted. The conclusion is that DevOps is suitable for use in a highly regulated environment in software development when the use is considered and planned. There are no impenetrable barriers to the use of DevOps due to regulations or compliance reasons, but a highly regulated environment poses challenges, and to address them we introduced the term DevOpsQa, which introduces quality assurance as an integral part of DevOps operations. The conclusion is also that DevOps is suitable for the case company, and it creates value for the case company when DevOpsQa are implemented in suitable processes. This thesis provides insights, recommendations, and best practices for software and systems development with DevOps practices in a highly regulated environment. This thesis emphasizes the need to review current software development processes, evaluate the improvement points, study applicable regulations, and consider the impact of these when applying DevOps into a highly regulated environment.
Keywords: DevOps, highly regulated environment, SDLC, agile, software development, HRE, MDR, medical software, software development life cycle, DevOpsQa